The Effect of Ergonomic Facility Management and Organizational Culture on Job Engagement through Quality of Work Life - Simon Petrus; Imam Nazarudin Latif; Evi Kurniasari Purwaningrum; Erialdi Syahrial (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Human resources quality and job engagement are crucial to support high-pressure immigration services and ensure optimal, accountable public service delivery. This study examines whether environmentally ergonomic-based facility management and organizational culture influence job engagement among immigration office civil servants in the East Kalimantan-North Kalimantan region, and whether these effects operate through perceived quality of work life. Survey data from 397 civil servants were analyzed using partial least squares structural equation modeling with bootstrapping to estimate both direct and mediated relationships among the constructs. The results show that environmentally ergonomic-based facility management and organizational culture significantly improve the quality of work life, while neither variable has a significant direct effect on job engagement. Quality of work life exerts a strong positive effect on job engagement and fully transmits the effects of both workplace factors to engagement, indicating that improvements in engagement occur primarily when employees experience safer and healthier conditions, stronger development opportunities, and better work-life balance. The study discusses these patterns as evidence that public sector engagement initiatives are most effective when ergonomic and cultural interventions are integrated with programs that explicitly strengthen employees’ quality of work life.